2013
DOI: 10.1186/1479-5868-10-111
|View full text |Cite
|
Sign up to set email alerts
|

Testing a self-determination theory model of children’s physical activity motivation: a cross-sectional study

Abstract: BackgroundUnderstanding children’s physical activity motivation, its antecedents and associations with behavior is important and can be advanced by using self-determination theory. However, research among youth is largely restricted to adolescents and studies of motivation within certain contexts (e.g., physical education). There are no measures of self-determination theory constructs (physical activity motivation or psychological need satisfaction) for use among children and no previous studies have tested a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
195
2
3

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 182 publications
(219 citation statements)
references
References 37 publications
19
195
2
3
Order By: Relevance
“…Children's autonomous motivation for sports was measured with the Dutch version of an adapted form of the Behavioral Regulations in Exercise Questionnaire (BREQ, Markland & Tobin, 2004;Sebire, Jago, Fox, Edwards, & Thompson, 2013). The adapted BREQ was validated in previous research (Sebire et al, 2013) and compared to the original BREQ, it contains fewer items to reduce participant burden and to keep the main focus on measuring the quality of children's motivation.…”
Section: Autonomous Motivation For Sportsmentioning
confidence: 99%
See 1 more Smart Citation
“…Children's autonomous motivation for sports was measured with the Dutch version of an adapted form of the Behavioral Regulations in Exercise Questionnaire (BREQ, Markland & Tobin, 2004;Sebire, Jago, Fox, Edwards, & Thompson, 2013). The adapted BREQ was validated in previous research (Sebire et al, 2013) and compared to the original BREQ, it contains fewer items to reduce participant burden and to keep the main focus on measuring the quality of children's motivation.…”
Section: Autonomous Motivation For Sportsmentioning
confidence: 99%
“…The adapted BREQ was validated in previous research (Sebire et al, 2013) and compared to the original BREQ, it contains fewer items to reduce participant burden and to keep the main focus on measuring the quality of children's motivation. Six items starting with the stem "I participate in sports because…" were used to measure autonomous motivation ( = 0.84; e.g., "I participate in sports because I enjoy participating in sports.").…”
Section: Autonomous Motivation For Sportsmentioning
confidence: 99%
“…SDT offers a comprehensive explanatory framework to study antecedents and outcomes of motivation to be physically active (Ng et al, 2012), incorporating many of the variables that have been identified as being relevant to physical activity (Sebire, Jago, Fox, Edwards, & Thompson, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…The underlying principles of SDT are that self-determined (autonomous) motivation is behaviourally and psychologically adaptive and that it develops to the extent that individuals perceive a sense of ownership or autonomy over their PA, feel able and competent and are supported in their PA by meaningful social relationships. 45,47 This hypothesis is supported by empirical research in the PA/exercise domain among children, 48 adolescents 49 and dancers. 50 Six motivation types are proposed in SDT, varying in their degree of self-determination or autonomy.…”
Section: Theories Of Behaviour Change: Self-determination Theory In Pmentioning
confidence: 50%